Qualities valued in nursing staff working with women with a diagnosis of borderline personality disorder in secure care: a multi-perspective study - Ratcliffe, Joanne Marie (The journal of forensic psychiatry & psychology, 2021)
The approach to female secure care has received increased attention over recent years, with an emphasis on relational security and recovery within the context of therapeutic relationships, but research on the views and experiences of service users regarding their relationships with staff is limited. This study explored the qualities valued in nursing staff working with women with a diagnosis of Borderline Personality Disorder (BPD) from the perspectives of service users and managers of asecure service. Semi-structured interviews with five service users and five managers were analysed using Interpretative Phenomenological Analysis. Three superordinate themes emerged: i) therapeutic relationships; ii) approach and manner; and iii) coping in a challenging environment. The findings revealed similarities in service user and manager perspectives of what is valued in nursing staff; however, a qualitative difference was noted in emphasis of interpersonal skills for service users; and risk management, boundaries and self-management for managers. The findings highlight the importance of research into service user experiences of secure care and representation of service user perspectives in staff recruitment and training.